Numerical study of the mixed convection flow over a square cylinder - Lafta Ghashim Jassim, Sajida (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
In this work, a numerical study is performed to predict the solution of two – dimensional, steady and laminar mixed convection flow over a square cylinder placed symmetrically in a vertical parallel plate. A finite difference method is employed to solve the governing differential equations, continuity, momentum, and energy equation balances. The solution is obtained for stream function, vorticity and temperature as dependent variables by iterative technique known as successive over relaxation. The flow and temperature patterns are obtained for Reynolds number and Grashof number at (Re= -50,50,100,-100) (positive or negative value refers to aidding or opposing buoyancy , +1 assisting flow, -1 opposing flow) and (102 to 105) , respectively. The results displaced that the recirculation length above the cylinder increases with the increase in Gr number and the average Nu number is the highest at the lower surface of the cylinder, while is the lowest at the top of the cylinder surface. A comparison between the obtained results and the published computational studies has been made and it showed a good agreement.